2018
DOI: 10.15406/jamb.2018.07.00184
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship of asiatic hard clam populations collected in northern coastal provinces in vietnam based on mtDNA sequence analysis

Abstract: The genetic relationship of some Asiatic hard clam (Meretrix meretrix) based on mtDNA COI sequence analysis was investigated for populations collected in Thai Binh, Nam Dinh, Nghe An provinces in Vietnam. In addition, this research also targets at species identification based on COI sequences. In total of 59 sequences analyzed, 19 sequences belonged to Meretrix meretrix species with Gen Bank accession number DQ399399.1. 17 sequences of M. meretrix were used for genetic relationship analysis among 3 populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This pattern is generated by new mutations accumulation in a sudden population expansion (Chu et al 2012). This genetic diversity pattern was reported in various clam species including Donax vittatus (Fernández-Pérez et al 2017), M. petechialis (Wang et al 2017a), and M. meretrix (Trang et al 2018). Generally, nucleotide diversity displays the mean number of differences among all pairs of haplotypes in each population and used to discuss a genetic diversity in the population (Ma et al 2010).…”
Section: Genetic Diversitymentioning
confidence: 88%
See 1 more Smart Citation
“…This pattern is generated by new mutations accumulation in a sudden population expansion (Chu et al 2012). This genetic diversity pattern was reported in various clam species including Donax vittatus (Fernández-Pérez et al 2017), M. petechialis (Wang et al 2017a), and M. meretrix (Trang et al 2018). Generally, nucleotide diversity displays the mean number of differences among all pairs of haplotypes in each population and used to discuss a genetic diversity in the population (Ma et al 2010).…”
Section: Genetic Diversitymentioning
confidence: 88%
“…The nucleotide sequencing of mtDNA COI has been used for studies population genetic structure of various clams such as Tridacna crocea and T. squamosa (Neo and Todd 2012), Atrina pectinata (Xue et al 2014), and M. petechialis (Zheng et al 2019). Several population genetic structure studies on M. meretrix have been revealed in Vietnam (Trang et al 2018) and China (Gu et al 2015) but no studies have been reported from Thailand. The genetic information of the genetic structure in marine species is essential to the management of marine resources, especially when sharing information with biological studies, such as reproduction, behavior, and spawning time.…”
Section: Introductionmentioning
confidence: 99%